Investigating the interplay between Grade 9 learners' home visual literacy and their development of school visual literacy in English First Additional language classrooms - Mnyanda, Lutho (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2017)
Visual literacy is one of the critical aspects that English First Additional Language teachers and learners battle with. The focus of this investigation was on developing learners' performance in visual literacy and helping teachers improve teaching practice. This thesis reports on efforts in developing critical visual literacy in two Grade 9 classrooms; a rural and a township school in the King William's Town District in the Eastern Cape. The research spread over four week, spending two weeks at each school as an ethnographic researcher, being assimilated to the culture of the each school. In understanding the kind of visual knowledge that these learners brought from home between the rural-urban divide, the learners displayed an interest in visual literacy, used the necessary language and appeared to design certain visual materials around the school. Data was collected in the form of questionnaires that learners filled, informal Facebook conversation screenshots, as well as the researcher's field notes. Learner focus group discussions were conducted, tape recorded and transcribed. Two lessons each were observed with the two teachers, and these were recorded and transcribed. A camera was used to take shots in the classroom to show the interaction between the teachers and the learners. Also, semi-structured interviews were held with each teacher and these were recorded and transcribed. The data revealed that there were no major differences between rural and urban school learners. However, the research has provided a valuable insight into the mismatch between home visual literacy practices and school visual literacy teaching. The learners' digital visual literacy practices were far ahead than those of the teachers who are not able to capitalise on these visual skills; the cultural capital that learners bring to school. Learners also displayed a low reading culture but the medium for reading has shifted considerably and learners developed communication skills through digital technology. Teacher agency in the classroom revealed that teachers need to first engage with the cognitive functions of the visual images that they teach by the prevalence of low level questions that they ask. Moreover, there is a place for translanguaging in visual literacy lessons. These indicate important areas for teacher development to promote the emergence of transformative agency.
Keywords: Visual literacy; Digital literacy; Action theory; Culturally relevant pedagogy; English language -- Study and teaching -- Foreign speakers -- Case studies; English language -- Study and teaching -- Foreign speakers -- South Africa -- Eastern Cape